(untitled) (KASBIT Business Journal, 2017)
The new millennium education priorities have led the policy makers to modify the higher education curriculum in accordance with the international standards. Thus, the curriculum standards across the country were forced to be uniform since the inception Higher Education Commission (HEC) in Pakistan. The universities under HEC are not allowed to modify or localize the curricula according to local needs, requirements and capacities. This paper in a phenomenological way evaluates the effect of reforms related to uniform curriculum standards on students, teachers and universities of backward areas in the country. The study highlights problems related to HEC curriculum; taken ‘economics’ discipline as a case study. The study calls for the revisit of other curriculums already in place and re-assess in lieu of local needs, requirements and capacities in the context of uniformity and localization. The paper provides a road map from localization of curriculum to uniform curriculum standards based on combined framework of bottom-up and top-down approach. The former approach involves all stakeholders at different tiers for the curriculum development, while the latter one deals with trainings and providing forum / platform for the coordination between the faculty members and curriculum developers.